Mechanism of action of over-expressing NY-ESO-1 in vesicular stomatitis virus and its combination therapy with NY-ESO-1 TCR-T - Tian, Ting; Ma, Liang; Mao, Liying; Wang, Xiangxiang; Cheng, Longxin; Ma, Qibin; Xu, Rong; Zhou, Guoqing (Frontiers in Immunology, 2025)
IntroductionVesicular stomatitis virus (VSV) is a promising oncolytic viral platform due to its short replication cycle, broad tissue tropism, low natural infection rate in humans, and a small genome that is easy to genetically manipulate. Leveraging these advantages, we developed an attenuated oncolytic VSV-based virus, OVV-01, encoding the tumor-associated antigen (TAA) NY-ESO-1.MethodsOVV-01 was constructed by inserting the NY-ESO-1 gene into a VSV backbone. In vitro cytotoxicity assays were performed across various tumor cell lines to evaluate its oncolytic activity. The expression and presentation of NY-ESO-1 on infected cells were assessed. In vivo studies using xenograft mouse models were conducted to examine tumor selectivity, T cell activation, and therapeutic efficacy, both alone and in combination with NY-ESO-1-specific TCR-engineered T cells.ResultsOVV-01 efficiently infected and inhibited the growth of multiple tumor cell lines in vitro. The overexpressed NY-ESO-1 was presented on the tumor cell surface and recognized by NY-ESO-1-specific TCR-T cells, promoting targeted cytotoxicity. In vivo, OVV-01 selectively replicated in tumor tissues and induced stronger activation of hCD4⁺, hCD8⁺, and NY-ESO-1-specific TCR-T cells compared to the control virus OVV-00. Combination therapy with OVV-01 and TCR-T cells significantly enhanced tumor control compared to monotherapies.DiscussionOur findings demonstrate that OVV-01 not only possesses potent direct oncolytic activity but also enhances the efficacy of adoptive T cell therapy by improving antigen presentation and T cell activation. This dual mechanism provides a rationale for using OVV-01 in combination immunotherapy strategies targeting solid tumors.